2014
DOI: 10.1093/mnrasl/slu168
|View full text |Cite
|
Sign up to set email alerts
|

The non-thermal superbubble in IC 10: the generation of cosmic ray electrons caught in the act

Abstract: Superbubbles are crucial for stellar feedback, with supposedly high (of the order of 10 per cent) thermalization rates. We combined multiband radio continuum observations from the Very Large Array (VLA) with Effelsberg data to study the non-thermal superbubble (NSB) in IC 10, a starburst dwarf irregular galaxy in the Local Group. Thermal emission was subtracted using a combination of Balmer Hα and VLA 32 GHz continuum maps. The bubble's nonthermal spectrum between 1.5 and 8.8 GHz displays curvature and can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…Observational constraints for processes related to rotating black holes may be taken from measurements of type Ic supernovae associated with GRBs (e.g., Mazzali et al 2014), which are around 10 52 erg. Heesen et al (2015) found 10 52 erg in a superbubble around the >23 M black hole IC10-X1, plausibly related to a hypernova at its formation. If the strong explosions would be connected to a particular range of stellar masses, they might occur in a small time interval.…”
Section: Energy Productionmentioning
confidence: 91%
“…Observational constraints for processes related to rotating black holes may be taken from measurements of type Ic supernovae associated with GRBs (e.g., Mazzali et al 2014), which are around 10 52 erg. Heesen et al (2015) found 10 52 erg in a superbubble around the >23 M black hole IC10-X1, plausibly related to a hypernova at its formation. If the strong explosions would be connected to a particular range of stellar masses, they might occur in a small time interval.…”
Section: Energy Productionmentioning
confidence: 91%
“…IC 10 was observed using the VLA in D-configuration at a central frequency of 6.2 GHz (project code: AH1006; Heesen et al 2015). To mitigate the effects of missing largeangular scale emission in these interferometric observations, single-dish data observed using the Effelsberg 100-m telescope were added to obtain total intensity image at 9.4 × 7.3 arcsec 2 angular resolution and rms noise of 15 µJy beam −1 (see Heesen et al 2015, for details).…”
Section: 2 Ghzmentioning
confidence: 99%
“…The 26 Al measurement constitutes another piece of statistical information for bubbles and superbubbles. 26 Al decays on a timescale of 1 Myr, much shorter than typical superbubble lifetimes (e.g., Oey & García-Segura 2004;Bagetakos et al 2011;Heesen et al 2015). Hence, we may expect it to reflect internal dynamics.…”
Section: Introductionmentioning
confidence: 95%